HOTEL MADANI (SYARIAH) PUBLIC RELATIONS COMMUNICATION STRATEGY IN IMPROVING THE QUALITY OF SERVICES TO GUESTS - Imam Jasri Nasution; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: This study aims to find out how forms of Public Relations communication at the Madani Hotel in carrying out their duties, especially their duties as intermediaries between the hotel and its guests. In this study, the authors used a type of qualitative research. Using descriptive analysis method. The subject of this research is public relations at Madani Hotel, while the object of this research is the public relations strategy at Madani Hotel in building its image. The author conducted research in September 2022 until it was completed. Place jl. Sisingamangaraja jl. Amaliun No 1, Kotamatsum No III, Kec. Medan City, Medan City, North Sumatras. Data Collection Techniques namely by direct observation, interviews, and documentation. After the data is collected, the writer analyzes the data. The results of this study indicate that the communication strategy used by Madani Hotel Public Relations is a promotion strategy and a sharia service strategy. The promotion strategy applied in Madani hotels is through print media (advertising in newspapers) and through sales calls. Sharia Service Strategies include not accepting spouses who are not of the same marriage, not providing alcoholic and non-halal food and drinks, each room has the Al-Quran, prayer books, prayer mats, and Qibla direction. The form of public relations communication for Madani hotels is by mass communication (sales calls) and between individuals (forms of service that are created that are comfortable and with sharia principles) Keywords: Communication Strategy, Public Relations, Service Quality